Inteligencja emocjonalna a poczucie skutecznosci kadry trenerskiej i instruktorskiej w zapasach - Rutkowska, K.; Gierczuk, D. (Polish Journal of Sport and Tourism, 2012)
The aim of this study was to diagnose the level of emotional intelligence and sense of efficiency among the occupational group of coaches and instructors in wrestling. Material and methods. The study involved 27 participants of a training course for coaches and instructors in training (25 men and 2 women). The basic methods of research involved the Emotional Intelligence Questionnaire INTE and the GSES scale for measurement of the sense of efficacy. Their use allowed us to diagnose the average level of emotional intelligence and the sense of self-efficacy. Results. Coaches and instructors are characterised by average level of emotional intelligence and the sense of self-efficacy. First class coaches are characterized by significantly higher levels of emotional intelligence, and the belonging to the group of trainers has no influence on the sense of efficacy. Conclusions. The results of the study can provide guidance to create/modify training programs for sports coaches. Developing mental toughness and improving emotional intelligence should occupy a special place in the training process wrestlers.